The Effect of Different Storage Conditions on Phytochemical Composition, Shelf-Life, and Bioactive Compounds of Voghiera Garlic PDO - Paola Tedeschi; Federica Brugnoli; Stefania Merighi; Silvia Grassilli; Manuela Nigro; Martina Catani; Stefania Gessi; Valeria Bertagnolo; Alessia Travagli; Maria Fiorenza Caboni; Alberto Cavazzini (MDPI AG, 2023)
Voghiera garlic is an Italian white garlic variety which obtained in 2010 the Protected Designation of Origin. It is widely used for culinary purposes or as an ingredient for supplement production due to its phytochemical compositions. The storage conditions seem to be crucial to retain the high quality of garlic bulbs and their by-products, taking into account the high importance of organosulfur and phenolic compounds for the bioactive potency of garlic and its shelf-life. This study aims to examine the effect of storage on the phytochemical composition, biological effects, and shelf-life of Voghiera garlic PDO. In detail, we considered (i) −4 °C (industrial storage) for 3, 6, and 9 months; (ii) +4 °C for 3 months (home conservation), and (iii) −4 °C for 3 months, plus +4 °C for another 3 months. We focused our attention on the organosulfur compounds, total condensed tannins, flavonoids, phenolic compounds, and related antioxidant activity changes during the storage period. To evaluate the bioactive effects, the Voghiera garlic extracts at different storage conditions were administered to a breast cancer cell line, while antioxidant and anti-inflammatory activity was detected using macrophage RAW 264.7 cells. We observed a decrease in sulfur compounds after 6 months which correlated to a decrease in bioactive effects, while the number of antioxidant compounds was stable during the storage period, showing the good effect of refrigerated temperature in maintaining garlic bulb shelf-life.